Climate drives community‐wide divergence within species over a limited spatial scale: evidence from an oceanic island. (25th November 2019) - Salces‐Castellano, Antonia; Patiño, Jairo; Alvarez, Nadir; Andújar, Carmelo; Arribas, Paula; Braojos‐Ruiz, Juan José; del Arco‐Aguilar, Marcelino; García‐Olivares, Víctor; Karger, Dirk N.; López, Heriberto; Manolopoulou, Ioanna; Oromí, Pedro; et al.
Abstract: Geographic isolation substantially contributes to species endemism on oceanic islands when speciation involves the colonisation of a new island. However, less is understood about the drivers of speciation within islands. What is lacking is a general understanding of the geographic scale of gene flow limitation within islands, and thus the spatial scale and drivers of geographical speciation within insular contexts. Using a community of beetle species, we show that when dispersal ability and climate tolerance are restricted, microclimatic variation over distances of only a few kilometres can maintain strong geographic isolation extending back several millions of years. Further to this, we demonstrate congruent diversification with gene flow across species, mediated by Quaternary climate oscillations that have facilitated a dynamic of isolation and secondary contact. The unprecedented scale of parallel species responses to a common environmental driver for evolutionary change has profound consequences for understanding past and future species responses to climate variation. Abstract : Using a community of beetle species, we show that when dispersal ability and climate tolerance are restricted, microclimatic variation over distances of only a few kilometres can maintain strong geographic isolation extending back several millions of years. Further to this, we demonstrate congruent diversification with gene flow across species, mediated by Quaternary climate oscillations that have facilitated a dynamic of isolation and secondary contact.